Criminal Liability for Professional Negligence under the Iraqi Penal Code - Saleh Mahdi, Assist. Lect. Huda (Basra studies journal, 2026)
This research examines criminal liability for professional negligence within the framework of public service. It analyzes the legal foundations governing the accountability of public employees for acts of omission or breaches of duty, whether the negligence is gross or causes harm to the public interest. The study clarifies the nature of penalties and the elements of the crime—physical, mental, and special—as well as the causal link between the act and the resulting harm. The research concludes that criminal liability for professional negligence serves as a fundamental tool to protect public order and the public interest. Clear legal provisions and precise definitions of criminal elements contribute to achieving justice and ensuring that penalties correspond to the severity of the harm caused. The study further highlights the importance of administrative oversight and continuous employee training to reduce negligence, emphasizing the need to balance punishment with justice to ensure both general and specific deterrence.